(untitled) (Al-Aasar, 2026)
Background: Contemporary Pakistani society is undergoing rapid socio-economic and cultural transformation, producing increasing divergence between older and younger generations in how problems are perceived and managed. These differences are particularly visible in coping narratives, mental health interpretations, and family-based decision-making systems. Objective: This narrative review synthesizes interdisciplinary literature to examine how generational cohorts in Pakistan construct problem perception and coping frameworks, and how these are shaped by structural transformations including economic precarity, family system transitions, and digital media exposure. Methods: A structured narrative synthesis was conducted on peer-reviewed literature (2019–2026) sourced from PsycINFO, PubMed, Google Scholar, and HEC-recognized journals. The analysis followed thematic coding procedures focusing on generational coping, mental health discourse, family systems, and socio-economic stressors. Results: Findings indicate a structural shift from collectivist, endurance-based coping frameworks (e.g., sabr, familial compromise, relational obligation) among older cohorts toward individualized, psychologically oriented coping frameworks emphasizing boundaries, emotional validation, and financial autonomy among younger cohorts. These differences are not purely attitudinal but emerge from interacting structural conditions including inflationary pressure, weakening joint family systems, gender role renegotiation, and digital exposure to global psychological discourses. Conclusion: Generational divergence in Pakistan reflects historically situated adaptations rather than cultural erosion. Effective intervention requires culturally integrated mental health frameworks, intergenerational dialogue mechanisms, and structural policy responses addressing economic insecurity and youth vulnerability.